Changes in the physicochemical property and sensory quality of heat‐processed beef flavour in the storage process. (14th November 2022) - Zhang, Zeyu; Zeng, Hong; Wang, Bei; Zhang, Dong; Cao, Yanping
Summary: This study aimed to investigate changes in the quality of heat‐processed beef flavour (HPBF) during 168‐day storage period at 4, 20 and 50 °C through evaluating 10 physicochemical indexes and sensory profiles. The sensory score of HPBF reduced dramatically at 50 °C compared with those at other temperatures. The correlation analysis indicated that among the 10 physicochemical indexes, oxidation–reduction potential (ORP), which is positively correlated to lipid oxidation, possessed the strongest association with the total sensory score of HPBF. The kinetic analysis showed that the increasing rate of ORP during the first 50‐day period at 50 °C was more than 10 times larger than those at 4 and 20 °C. These results suggested that lipid oxidation played a major role in affecting the quality of HPBF, especially during the early storage period. Reducing lipid oxidation via for instance maintaining a relatively low storage temperature should be given better attention for obtaining high‐quality HPBF. Abstract : The changes in physicochemical indexes and sensory evaluation of heat‐processed beef flavour were measured over an extended storage period (168 days), which provided a basis for the development and storage of the processed‐meat flavourings with high quality.